How champions think in sports and in life - Rotella, Robert J. (New York Simon & Schuster, 2015)
Acclaimed sports psychologist Bob Rotella has advised everyone from professional golfers to NBA superstars to business executives on how to flourish under pressure and overcome challenges. Now, for the first time, he's distilled his decades of in-depth research and practical experience into a potential-unlocking guide for everyone. The audiobook is not a collection of Rotella's theories; it consists of performance principles that have proven themselves in countless competitive situations.
Title from container.
Keywords: Sports--Psychological aspects